Red blood cell alloimmunisation in multi-transfused patients from an haemodialysis service in Burkina Faso - Koumpingnin Nebie; Salam Sawadogo; Salifo Sawadogo; Jérôme Koulidiati; Habi Y.A. Lengani; Abdoul G. Sawadogo; Jérôme Babinet; Mohammed Khalloufi; Saliou Diop; Eléonore Kafando (AOSIS, 2022)
Background: In Burkina Faso, red blood cell (RBC) transfusion remains the crucial anaemia treatment following chronic renal failure (CRF) as erythropoietin and its analogues are unavailable. However, blood group matching beyond the ABO and Rhesus is not common in Burkina Faso. Thus, alloimmunisation is a potential issue for transfused patients. Objective: Our study aimed to identify anti-erythrocyte antibodies in multi-transfused CRF patients at the Yalgado Ouedraogo Teaching Hospital, Ouagadougou, Burkina Faso. Methods: This cross-sectional study, conducted from October 2018 to November 2019, included CRF patients who had received at least two RBC units. We screened patients for the presence of RBC antibodies using three commercial Cells panels and identified antibody specificities for positive screenings using 11 Cells panels for an indirect antiglobulin test (IAT) in a low ionic strength microcolumn gel-card system. Results: Two hundred and thirty-five patients (45.1% female; average age: 41.5 years) were included. The median number of blood units received per patient was 10 (interquartile range: 5-20). The overall alloimmunisation rate was 5.9% (14/235). Antibodies identified included: anti-D (1 case), anti-C (1 case), anti-D+C (4 cases), anti-CW (1 case), anti-E (1 case), anti-S (1 case) and anti-Lea (1 case). In four positive patients, the specificity of the antibodies was indeterminate. No risk factors were associated with alloimmunisation. Conclusion: In Burkina Faso, screening for RBC alloantibodies should be mandated for patients at risk. The high rate of indeterminate antibodies suggests the need to develop a local RBC antibody panel adapted to the local population.